2018
DOI: 10.15407/frg2018.02.124
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF CHITOSAN OF DIFFERENT ORIGINS ON THE CONTENTS OF PHENOLIC ANTIOXIDANTS IN <i>FRAGARIA ANANASSA</i> DUCH. LEAVES

Abstract: Plants are subjected to an enormous number of biotic and abiotic environmental stresses during their life cycle. The responses to different stresses are very complex and include changes at the transcriptome, cellular, and physiological levels. The recognition of inductors and signaling molecules is one of the ways of inducting the plant's own defense mechanisms. The response reactions of Fragaria ananassa Duch. plants treated with chitosan of different origins and molecular weight were studied in our experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The most significant response reaction to stress factor or action of elicitor is the oxidation of phenolic compounds and the synthesis of phytoalexins (Volynets, 2013). Our previous study showed that the synthesis of phenolic compounds in Fragaria ananassa plants is quite mobile and sensitive to external factors (Subin et al, 2018). It is also known that a significant difference exist in the synthesis of phenolic compounds in different plant species (Babenko et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most significant response reaction to stress factor or action of elicitor is the oxidation of phenolic compounds and the synthesis of phytoalexins (Volynets, 2013). Our previous study showed that the synthesis of phenolic compounds in Fragaria ananassa plants is quite mobile and sensitive to external factors (Subin et al, 2018). It is also known that a significant difference exist in the synthesis of phenolic compounds in different plant species (Babenko et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Another research showed that superoxide dismutase (SOD) and phenylalanine ammonia-lyase (PAL) were overexpressed in chitosan-treated grapes (Bavaresco et al, 2017). Previous studies have demonstrated differences in the physiological reactions of the plants Nicotiana tabacum and Fragaria ananassa to treatment with chitosans of different biological origin, molecular weight, and degree of deacetylation (Subin et al, 2018). It was also noted that this biopolymer acts as a potent inducer of phytoalexin synthesis and accumulation (Köhle et al, 1984), and triggers the formation of callose (Benhamou and Nicole, 1999) in the processes of lignification and in the production of proteinase inhibitors (Hirano et al, 1999) in various pathosystems (El Hadrami et al, 2010).…”
Section: Introductionmentioning
confidence: 99%